Formation of functional literacy of primary school students through the development of speech activity - Жусупбекова, Гульсара; Жұмаділ, Ақбота (Pedagogy and Psychology, 2020)
The article considers the problem of the formation of functional literacy of a primary school student through the development of speech activity. The relevance of the issue of the formation of functional literacy of students is repeatedly touched upon in legal acts in the field of education, which clearly indicate is importance among the younger generation in the education of a competitive personality that meets modern requirements. Based on a theoretical analysis of the ideas and views of foreign and domestic scientists, the author determins the constituent components in the structure of the concept of a functionally competent person. It reveals in a board sense the definition of the term “speech activity”. Summarizes the nature of the types of speech activity: listening, speaking, reading and writing. She notes that the study of subjects frim the educational field “Language and Literature” is of geat importance in the formation of the functional literate personality of students in the educational process of primary school, while the update educational content, through cross-cutting topics, contributes to the development of cognitive abilities, self- esteem, critical thinking, and adaptation to the environment.